The Dark Side of Silicon Energy Efficient Computing in the Dark Silicon Era - Rahmani, Amir M.; Liljeberg, Pasi; Hemani, Ahmed; Jantsch, Axel; Tenhunen, Hannu (Springer International Publishing : Imprint: Springer, 2017)
This book presents the state-of-the art of one of the main concerns with microprocessors today, a phenomenon known as "dark silicon". Readers will learn how power constraints (both leakage and dynamic power) limit the extent to which large portions of a chip can be powered up at a given time, i.e. how much actual performance and functionality the microprocessor can provide. The authors describe their research toward the future of microprocessor development in the dark silicon era, covering a variety of important aspects of dark silicon-aware architectures including design, management, reliability, and test. Readers will benefit from specific recommendations for mitigating the dark silicon phenomenon, including energy-efficient, dedicated solutions and technologies to maximize the utilization and reliability of microprocessors. Enables readers to understand the dark silicon phenomenon and why it has emerged, including detailed analysis of itsimpacts; Presents state-of-the-art research, as well as tools for mitigating the dark silicon phenomenon; Includes coverage of various aspects of dark silicon awareness in design, management, reliability, and tests.